2004
DOI: 10.1677/joe.0.1820183
|View full text |Cite
|
Sign up to set email alerts
|

Is estrogen receptor alpha key to controlling bones' resistance to fracture?

Abstract: The ability of bones to withstand functional loading without damage depends upon their cell populations establishing and subsequently maintaining a mass and architecture that are appropriately robust for the purpose. In women, the rapid loss of bone associated with the menopause represents a steplike decline in the effectiveness of this process with consequent increase in bone fragility. In men, loss of bone tissue and reduction in bone strength are more gradual and the increased incidence of fragility fractur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0
6

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 79 publications
1
32
0
6
Order By: Relevance
“…Earlier studies have demonstrated that female but not male mice with ERα inactivation display reduced cortical osteogenic bone response to mechanical loading (19,(21)(22)(23)(24). To determine if the reduced osteogenic response to mechanical loading in female ERα −/− mice is caused by a lack of ERα in osteocytes, we loaded tibiae of female Dmp1-ERα −/− mice and WT mice using a standardized axial loading procedure.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Earlier studies have demonstrated that female but not male mice with ERα inactivation display reduced cortical osteogenic bone response to mechanical loading (19,(21)(22)(23)(24). To determine if the reduced osteogenic response to mechanical loading in female ERα −/− mice is caused by a lack of ERα in osteocytes, we loaded tibiae of female Dmp1-ERα −/− mice and WT mice using a standardized axial loading procedure.…”
Section: Resultsmentioning
confidence: 99%
“…As female mice with total ERα inactivation display reduced cortical osteogenic bone response to mechanical loading (19,(21)(22)(23)(24), and osteocytes are thought to function as the main mechanosensors in bone, it was biologically plausible to hypothesize that ERα in osteocytes is important for the osteogenic response to mechanical loading. However, the cortical osteogenic bone response to mechanical loading was normal in Dmp1-ERα −/− mice, demonstrating that ERα in osteocytes is not crucial for the osteogenic response to mechanical loading and, therefore, further studies are required to identify the ERα target cell type contributing to the osteogenic response to mechanical loading.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The association between amenorrhea and low bone mass is well known (31). The mechanism is attributed to estrogen deficiency, which leads to an increased bone resorption, since estrogen has osteoprotective effects through specific estrogen receptor actions (32,33). Cortisol was also highly negatively correlated with spinal BMD.…”
Section: Discussionmentioning
confidence: 99%